RNA-seq based SNP discovery in liver transcriptome of Polish Landrace pigs - Pierzchała, Mariusz; Ogłuszka, Magdalena; Goluch, Dorota; Poławska, Ewa; Blicharski, Tadeusz; Roszczyk, Agnieszka; Nawrocka, Agata; Urbański, Paweł; Stepanow, Kamila; Ciepłoch, Aleksandra; Sachajko, Mateusz; Skowroński, Mariusz; et al. (Translational Research in Veterinary Science, 2019)
Background: RNA-seq technology is most commonly used in quantitative measurement of gene expression levels and identification of non-annotated transcripts. It is also used for the coding SNPs (cSNPs) discoveries in an efficient and cost-effective way. The aim of this study was to identify the putative genetic cSNPs variants in liver transcriptome of Polish Landrace pigs fed with high and low (normal) omega-6 and omega-3 polyunsaturated fatty acids (PUFAs) diets. Methods: RNA-seq based NGS experiment was performed on Polish Landrace pigs fed with high and low PUFAs diets. Total RNA were isolated from liver tissues of low PUFAs (n=6) and high PUFAs dietary group (n=6) of Polish Landrace pigs. The RNA-seq libraries preparations were performed by mRNA enrichment, mRNA fragmentation, second strand cDNA synthesis, adaptor ligation, size selection and PCR amplification using the illumina TruSeq RNA Sample Prep Kit v2 (Illumina, San Diego CA, USA), followed by NGS sequencing on MiSeq illumina platform. The quality control (QC) of raw RNA-seq data of liver transcriptome was performed using the Trimmomatic and FastQC tools. The paired-end mapping of the liver transcriptome RNA-seq data (n=12) was performed on the reference genome Sus scrofa v.10.2, followed by cSNPs discovery using GATK and SAMtools bioinformatics SNPs caller tools. Results: Two pooled paired-end libraries of 151bp liver transcriptome of Polish Landrace pigs were generated from MiSeq instrument and subsequent Fastq RNA-seq data were submitted to NCBI SRA database (https://www.ncbi.nlm.nih.gov/sra). Our study identified 25.3 million paired-end reads: representing 13,509,248 paired-end reads of high PUFAs dietary group and 11,815,696 paired-end reads of low PUFAs dietary group of Polish Landrace pigs liver transcriptome. The SNP discovery results revealed identification of 25909 homozygous and 23290 heterozygous cSNPs in the liver transcriptome of both dietary groups of Polish Landrace pigs. With regards to same or alternative SNPs alleles encoding amino acids regions, a total of 27141 synonymous cSNP and 5989 non-synonymous cSNPs were identified in liver transcriptome representing high PUFAs dietary group. However, a total of 15128 synonymous cSNPs and 3900 non-synonymous cSNPs were identified in liver transcriptome representing low PUFAs dietary groups of Polish Landrace pigs. The identification of single nucleotide variations (SNVs) representing substitutions of all four possibilities (A,T,G,C) were ranged 2872 to 6868 SNVs (high PUFAs) and 2574 to 3654 SNVs (low PUFAs) in the homozygous cSNPs and 2452 to 2678 SNVs (high PUFAs) and 2094 to 2230 SNVs (low PUFAs) in the heterozygous cSNPs of liver transcriptomes of Polish Landrace pigs, respectively. Conclusions: Study concluded that identification of cSNPs dataset representing the liver transcriptome of Polish Landrace pigs fed with a control diet (low) and pigs fed with a PUFAs diet (high) may be helpful to develop a new set of genetic markers for trait-associated studies (viz., growth and metabolic traits) specific to Polish Landrace pig breed. Such cSNP markers eventually can be utilized in the genetic improvement of the pig production traits using the genome-wide association studies (GWAS) and to finally implement on marker assisted selection (MAS) and genomics selection (GS) program in active breeding population of Polish Landrace pigs in Poland.